Molecular Typing of Bluetongue Viruses Isolated Over a Decade in South India. Issue 5 (19th January 2015) - Reddy, Y. V.; Krishnajyothi, Y.; Susmitha, B.; Devi, B. V.; Brundavanam, Y.; Gollapalli, S. R.; Karunasri, N.; Sonali, B.; Kavitha, K.; Patil, S. R.; Sunitha, G.; Putty, K.; et al.
Summary: Bluetongue (BT) is an arthropod‐borne viral disease mostly of sheep. Bluetongue virus (BTV) is a segmented double‐stranded RNA virus belonging to the genus Orbivirus of family Reoviridae and is transmitted by midges belonging to Culicoides spp. The disease is endemic in the tropics and subtropics, and the incidence is high in southern India. Twenty‐six serotypes of BTV have been reported worldwide. Although most of the serotypes have been reported in India, information regarding currently circulating serotypes is essential to develop control programs. Both serological assays and nucleic acid‐based assays have been used for typing BTV. Segment 2, which codes for the outer capsid protein VP2, is the target for PCR‐based typing; however, the VP2 sequence diversity among viruses belonging to the same serotype but isolated from different geographical areas makes it essential to develop geographical based reagents. In this study, reverse transcription PCR was developed based on sequences of Indian isolates of BTV (serotypes 1, 2, 9, 10, 12, 16, 21 and 23), and this was applied to type 52 isolates obtained during the last decade. It was found that multiple serotypes circulate, with involvement of more than one serotype infecting individual animals and herds over a period in a given area. Detection of circulating serotypes and estimation of herd immunity against different serotypes of BTV may provide important information for predicting the distribution of these serotypes and inclusion of serotypes in vaccines.